56.9k views
5 votes
Solve for x: −2(x + 3) = −4(x + 1) − 4

User ChrisMM
by
4.9k points

2 Answers

0 votes

Answer:

x= 1/3

Explanation:

−2(x + 3) = −4(x + 1) − 4

−2x -6 = −4x - 4x − 4

-2x +4x + 4x= - 4x − 4 + 6

6x= − 4 + 6

6x= 2

x= 2/6

x= 1/3

User Arion
by
4.5k points
1 vote

Hello! My name is Chris and I’ll be helping you with this problem.

Date: 9/27/20 Time:

Answer:

x = -1

Explanation:

Step 1: Simplify both sides of the equation.

−2(x+3)=−4(x+1)−4

(−2)(x)+(−2)(3)=(−4)(x)+(−4)(1)+−4(Distribute)

−2x+−6=−4x+−4+−4

−2x−6=(−4x)+(−4+−4)(Combine Like Terms)

−2x−6=−4x+−8

−2x−6=−4x−8

Step 2: Add 4x to both sides.

−2x−6+4x=−4x−8+4x

2x−6=−8

Step 3: Add 6 to both sides.

2x−6+6=−8+6

2x=−2

Step 4: Divide both sides by 2.

2x = -2

/2 /2

x=−1

I hope this helped answer your question! Have a great rest of your day!

Furthermore,

Chris

User Mill
by
4.6k points